Analisis Pengaruh Karakteristik Individu, Pekerjaan dan Lingkungan Kerja Terhadap Motivasi dan Kinerja Tenaga Kerja Sukarela Pengumpul Sampah - Anita Melina Febriyanti; Ginta Ginting; Andriyansah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
The Environmental Agency of Rejang Lebong Regency is one of the Government Agencies that has assets of 277 volunteers in 2020, with 80 voluntary garbage collection workers. Human resources or voluntary workforce contribute and have an important role in the success and achievement of the agency's goals in this case the Rejang Lebong Environmental Agency. Based on data from The Hazardous and Non-Hazardous Waste Section in Rejang Lebong Environmental Agency in 2017, 2018 and 2019, the voluntary workforce of garbage collectors are able to collect waste as many as 14,999.82 tons, 15,191.71 tons and 16,230.88 tons tons or only 39.68%, 40.03%, and 42.65% of the targets planned by the Rejang Lebong Environmental Agency for 2017, 2018 and 2019 respectively 37,800 tons, 37,951.97 tons, and 38,103.78 tons. This shows that the targets achieved for 2017, 2018 and 2019 are still less than 50%. Based on the results of this research, it can be seen that there are several things that affect the motivation and performance of workers in achieving agency goals, including: job characteristics affect motivation, and individual characteristics, work environment, and motivation affect workforce performance.